Motion‐robust intensity‐modulated proton therapy for distal esophageal cancer. Issue 3 (8th February 2016) - Yu, Jen; Zhang, Xiaodong; Liao, Li; Li, Heng; Zhu, Ronald; Park, Peter C.; Sahoo, Narayan; Gillin, Michael; Li, Yupeng; Chang, Joe Y.; Komaki, Ritsuko; Lin, Steven H.
Abstract : Purpose: To develop methods for evaluation and mitigation of dosimetric impact due to respiratory and diaphragmatic motion during free breathing in treatment of distal esophageal cancers using intensity‐modulated proton therapy (IMPT). Methods: This was a retrospective study on 11 patients with distal esophageal cancer. For each patient, four‐dimensional computed tomography (4D CT) data were acquired, and a nominal dose was calculated on the average phase of the 4D CT. The changes of water equivalent thickness (ΔWET) to cover the treatment volume from the peak of inspiration to the valley of expiration were calculated for a full range of beam angle rotation. Two IMPT plans were calculated: one at beam angles corresponding to small ΔWET and one at beam angles corresponding to large ΔWET. Four patients were selected for the calculation of 4D‐robustness‐optimized IMPT plans due to large motion‐induced dose errors generated in conventional IMPT. To quantitatively evaluate motion‐induced dose deviation, the authors calculated the lowest dose received by 95% ( D 95) of the internal clinical target volume for the nominal dose, the D 95 calculated on the maximum inhale and exhale phases of 4D CT D CT 0 and D CT 50, the 4D composite dose, and the 4D dynamic dose for a single fraction. Results: The dose deviation increased with the average ΔWET of the implemented beams, ΔWETave . When ΔWETave was less than 5 mm, the dose error was less than 1 cobalt gray equivalent based on D CT 0 and D CT 50 . The dose deviation determined on the basis of D CT 0 and D CT 50 was proportionally larger than that determined on the basis of the 4D composite dose. The 4D‐robustness‐optimized IMPT plans notably reduced the overall dose deviation of multiple fractions and the dose deviation caused by the interplay effect in a single fraction. Conclusions: In IMPT for distal esophageal cancer, ΔWET analysis can be used to select the beam angles that are least affected by respiratory and diaphragmatic motion. To further reduce dose deviation, the 4D‐robustness optimization can be implemented for IMPT planning. Calculation of D CT 0 and D CT 50 is a conservative method to estimate the motion‐induced dose errors.